2018
DOI: 10.1111/cpr.12523
|View full text |Cite|
|
Sign up to set email alerts
|

The spatiotemporal expression and mineralization regulation of p75 neurotrophin receptor in the early tooth development

Abstract: Objective: The aim of this study was to investigate the spatiotemporal expression and potential role of p75NTR in tooth morphogenesis and tissue mineralization. Materials and methods:The dynamic morphology of the four stages (from the beginning of E12.5 d, then E13.5 d and E15.5 d, to the end of E18.5 d) was observed, and the expressions of p75NTR and Runx2 were traced. The ectomesenchymal stem cells (EMSCs) were harvested in vitro, and the biological characteristics were observed.Moreover, the mineralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…12 Moreover, p75NTR has been reported to participate in tooth morphogenesis and dental hard tissue mineralization. [13][14][15][16][17] However, most molecular signatures on the effect of p75NTR in tooth morphogenesis remain to be uncovered, and the elusive mechanism underlying tooth development has severely restricted dental tissue engineering thus far. In this study, p75N-TR ExIII -knockout mice and EMSCs isolated from p75NTR ExIII−/− and p75NTR +/+ male mice were investigated to reveal the exact mechanism of p75NTR in mineralization regulation, contributing to dental tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Moreover, p75NTR has been reported to participate in tooth morphogenesis and dental hard tissue mineralization. [13][14][15][16][17] However, most molecular signatures on the effect of p75NTR in tooth morphogenesis remain to be uncovered, and the elusive mechanism underlying tooth development has severely restricted dental tissue engineering thus far. In this study, p75N-TR ExIII -knockout mice and EMSCs isolated from p75NTR ExIII−/− and p75NTR +/+ male mice were investigated to reveal the exact mechanism of p75NTR in mineralization regulation, contributing to dental tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous report, 16 this study continued to investigate the potential mechanism of p75NTR in regulating mineralization.…”
Section: Potential Mechanism Of P75ntr In Regulating Mineralizationmentioning
confidence: 99%
“…It has been reported that p75NTR might participate in the regulation of rat tooth morphogenesis, especially dental hard tissue formation 21. Xing et al22 found that p75NTR‐positive EMSCs showed greater odontogenic differentiation ability than p75NTR‐negative EMSCs both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, studies showed that p75NTR to be a specific surface marker of neural crest-derived stem cells [ 26 ]. Thus, it can be used to purify neural crest-derived EMSCs and to regulate tooth morphogenesis, osteogenic differentiation and tissue mineralization [ 11 , 27 , 28 ]. In this study, p75NTR +/+ EMSCs show a higher proliferation and odonto/osteogenic differentiation than p75NTR −/− EMSCs.…”
Section: Discussionmentioning
confidence: 99%